A Reinforcement Learning System Embedded Agent with Neural Network-Based Adaptive Hierarchical Memory Structure - Obayashi, Masanao; Narita, Kenichiro; Okamoto, Yohei; Kuremoto, Takashi; Kobayashi, Kunikazu; Feng, Liangbing (IntechOpen, 2011)
None